2000
DOI: 10.1128/jb.182.17.4841-4848.2000
|View full text |Cite
|
Sign up to set email alerts
|

Relative Roles of the fla/che P A , P D-3 , and P sigD Promoters in Regulating Motility and sigD Expression in Bacillus subtilis

Abstract: Three promoters have been identified as having potentially important regulatory roles in governing expression of the fla/che operon and of sigD, a gene that lies near the 3 end of the operon. Two of these promoters, fla/che P A and P D-3 , lie upstream of the >26-kb fla/che operon. The third promoter, P sigD , lies within the operon, immediately upstream of sigD. fla/che P A , transcribed by E A , lies >24 kb upstream of sigD and appears to be largely responsible for sigD expression. P D-3 , transcribed by E D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 29 publications
3
45
1
Order By: Relevance
“…These results were confirmed and extended by antiflagellin immunoblot analysis performed as described previously (16). The level of flagellin protein was significantly reduced in the ylxL mutant LMB231 when compared to levels found in the wild-type strain (Fig.…”
Section: -Dependent Functionssupporting
confidence: 71%
See 3 more Smart Citations
“…These results were confirmed and extended by antiflagellin immunoblot analysis performed as described previously (16). The level of flagellin protein was significantly reduced in the ylxL mutant LMB231 when compared to levels found in the wild-type strain (Fig.…”
Section: -Dependent Functionssupporting
confidence: 71%
“…1). While sigD, located 26 kb from the major promoter for this operon, has been shown to be part of fla/che, (2,16), it was not known if ylxL is part of the fla/che transcription unit. Previous studies demonstrated that insertions between sigD and ylxL resulted in defects in chemotaxis (9,18), swimming (9), and motility (10).…”
Section: -Dependent Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In B. subtilis, the genes are cotranscribed from a common promoter under the control of RNA polymerase and the vegetative 70 homolog A . The genetic organization of the F3 locus of C. difficile suggests that a similar cotranscription of the F3 region genes from a common promoter may be occurring (45). Included in this group of early genes are fliF (MS ring), fliG, and fliM (C ring motor switch), flhB and fliR (export apparatus membrane proteins), and the fliA ( 28 homolog) transcriptional regulator of the F1 locus.…”
Section: Generation Of Flagellar Mutant Strainsmentioning
confidence: 99%